Influence of various storage conditions on rind breakdown and quality parameters in tangelo (Citrus reticulata Blanco x Citrus paradisi Macf.) - Pavel, E.W. (University of Pretoria, 2013)
Dissertation (MSc (Agric) Horticultural Science)--University of Pretoria, 2005.